Study and Design of Permanent Magnetic Levitation Roller of Belt Conveyor - Wu Huachun; Ren Yongwu; Yu Haitao; Shi Mengyao (Jixie chuandong)
The roller is an important component for the belt conveyor. The function of roller is supporting conveyor belt,to ensure the belt conveyor smooth operation. Aiming at overcoming the difficulties from the traditional roller with mechanical bearings frictional wear,which suffers from large rotational resistance,limited belt speed,high energy consumption. A new type of magnetic levitation roller is designed,which is supported by permanent magnetic bearing（ PMB）,but the axial force is restrained by mechanical force. The analysis formulas of PMB’s loading capacity,torque and stiffness are established based on the equivalent magnetic charge method. The parameters of magnet levitation roller are optimized by using MATLAB. By comparing with the finite element numerical method,the rationality of the permanent magnetic bearing designed by using equivalent magnetic charge method is verified. The test results of rotational resistance show that,the friction and running resistance can be effectively reduced by the proposed magnet levitation roller.